2016
DOI: 10.3171/2016.1.peds15676
|View full text |Cite
|
Sign up to set email alerts
|

Childhood hydrocephalus secondary to posterior fossa tumor is both an intra- and extraaxial process

Abstract: OBJECTIVE Ventricular dilation secondary to tumor obstruction of the posterior fossa CSF outflow in childhood is an intraaxial process. However, third ventriculostomy or complete tumor removal often fails to reduce the pressure in some children, and in others there is a delayed reduction in intracranial pressure; this is termed the adaptation period. The cause of this adaptation period has not been studied. Venous sinus compression is highly correlated with other for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
1
21
1
Order By: Relevance
“…The findings in external hydrocephalus are similar to a previous study, where 3/6 children had venous stenosis [12]. The findings in obstructed hydrocephalus also mirror previous findings [11,15] i.e. that a significant outflow stenosis rather than a presumed increase in CSF outflow resistance secondary to aqueduct occlusion predominates.…”
Section: Venous Stenosissupporting
confidence: 89%
See 2 more Smart Citations
“…The findings in external hydrocephalus are similar to a previous study, where 3/6 children had venous stenosis [12]. The findings in obstructed hydrocephalus also mirror previous findings [11,15] i.e. that a significant outflow stenosis rather than a presumed increase in CSF outflow resistance secondary to aqueduct occlusion predominates.…”
Section: Venous Stenosissupporting
confidence: 89%
“…Using the current methodology 11/17 or 65% had a significant outflow stenosis and 2/17 or 12% a non-significant stenosis. Twelve of these 17 patients (who had venous sinus stenosis) were the subject of a prior publication [15] and these were excluded to limit literature duplication. The clinical findings and follow-up for these patients can be found in this publication [15].…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that younger patients with posterior fossa are at higher risk for the development of persistent hydrocephalus. [3,4,15,21,22] Bognar et al [3] and Kumar et al [21] have demonstrated that age< 3 years at tumor surgery is a significant predictor of postoperative CSF diversion. This might be explained by the finding that the younger patient with…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism, like in the pial AVF, is unclear. 5,22 In this case, the arteriovenous shunt was considered the cause of hydrocephalus, and therapeutic embolization was planned. We speculate that excessive intracranial venous pressure can affect the paravascular pathway secondary to an inverted hydrodynamic flow.…”
Section: Discussionmentioning
confidence: 99%